Pension income inequality: a cohort study in six European countries - Neugschwender, Jörg (Luxembourg, 2014)
"This paper is an empirical overview of inequalities of pension outcomes in six European countries, which are shaped by a variety of institutional pensions schemes. The study contrasts pension system regulation in Denmark, Finland, Germany, Italy, Sweden and the United Kingdom; and analyses their impact on current pension income. The main focus is analyzing the current trends of income distribution using a birth cohort perspective. In addition, a detailed analysis of these trends is included by income quintiles/deciles and pension income sources. The study is a cohort design, where the data are pooled for 77251 individuals in six countries in 28 datasets covering multiple time periods from 1992 to 2010 using the Luxembourg Income Study (LIS) Database. The analyses show that pension incomes in these societies are diversified in terms of public vs. private pension income, purchasing power parities (PPP) adjusted income amounts, and the shape of the income distribution. The countries also differed strongly in relation to the general living standard in the respective societies."